Electronic properties of printed nanoparticulate silicon - Abass, Sara Abdelazeem Hassan (Department of Physics, 2014)
Printed silicon is an award-winning technology in the development of a large area of flexible electronics. In an investigation of the fundamental properties of printed nanoparticulate silicon composites, layers were screen printed and successfully characterised to establish their electrical performance using a Hall Measurement System (HMS). To explore properties of the nanoparticulate silicon composite a magnetoconductivity tensor model was developed and applied to extract parameters governing the electrical properties of the material. All the layers showed at least two carrier types. The effect of particle loading and temperature on the electrical properties was also investigated. Although carrier concentrations are generally low, their mobility was found to be comparable to, or even better than, similar classes of semiconductor materials.